Apparent resistant hypertension and the risk of vascular events and mortality in patients with manifest vascular disease. Issue 1 (January 2018) - van der Sande, Nicolette G.C.; de Beus, Esther; Bots, Michiel L.; Voskuil, Michiel; Blankestijn, Peter J.; Visseren, Frank; Spiering, Wilko
Abstract : Objective: Patients with apparent resistant hypertension (aRH) are at increased risk for developing cardiovascular disease. It is unknown if this condition is related to increased cardiovascular risk in patients with clinically manifest vascular disease. Methods: In 6191 hypertensive patients with clinically manifest vascular disease, we evaluated the risk of subsequent vascular events and mortality between patients with controlled hypertension, uncontrolled hypertension, controlled aRH, and uncontrolled aRH. Controlled aRH was defined as office blood pressure less than 140/90 mmHg while using at least four antihypertensive drugs. Uncontrolled aRH was defined as office blood pressure at least 140/90 mmHg while using three antihypertensive drugs including a diuretic, or at least four antihypertensive drugs. Outcomes of interest were myocardial infarction, stroke, cardiovascular mortality, the composite outcome of cardiovascular events, and all-cause mortality. Results: In total 2564 patients (41%) had controlled hypertension, 3063 patients (49%) had uncontrolled hypertension, 123 patients (2%) had controlled aRH, and 411 patients (7%) had uncontrolled aRH. During 7.1 years of follow-up patients with controlled aRH were at a higher risk of cardiovascular mortality [hazard ratios 1.86; 95% confidence interval (CI) 1.10–3.15], and all-cause mortality (hazard ratios 1.64; 95% CI 1.07–2.52) compared with patients with controlled hypertension. Patients with uncontrolled aRH were at a higher risk of cardiovascular mortality (hazard ratios 1.36; 95% CI 1.01–1.83), and higher risk of all-cause mortality (hazard ratios 1.27; 95% CI 1.01–1.60) compared with patients with controlled hypertension. Conclusion: In hypertensive patients with clinically manifest vascular disease, presence of controlled and uncontrolled aRH is related to an increased risk of cardiovascular mortality and all-cause mortality. Abstract : Supplemental Digital Content is available in the text